Respuesta :

Answer:

x=1 y=14

multiply x-y=-13 by 3 so the x would cancel out. solve for y

then plug in y to one of the equations to get x

Answer: the answer is x= -2 , y=11

Step-by-step explanation:

First

1: we have to find the answer for x in x-y= -13

2: add y on both sides of the equation

3: we will get x= -13+y

Second

1: Substitute x in 3x-y= -17 with x=-13+y

2: then you will get 3(-13+y)-y= -17

3: multiply 3 with -13 and y

4: you will get -39+3y-y =-17

5: add 3y and -y

6: you will get -39+2y= -17

7: add 39 on both sides of the equation

8: you will get 2y=22

9: divide 2 on both sides

10: you will get y= 11

Third

1: plug 11 for y in x= -13+y

2:  then you will get x= -13+11

3:  you will x= -2

So x= -2 and y= 11